2005
DOI: 10.1080/09064700500239453
|View full text |Cite
|
Sign up to set email alerts
|

Competitive behaviour of dairy cows at a concentrate self-feeder

Abstract: We investigated whether feeding cows are disturbed by butting of other cows during the time they are in a concentrate self-feeder, and whether this leads to concentrate leftovers. Forty dairy cows were observed while visiting two self-feeders. If a cow was butted visiting the self-feeder, it was considered as 'disturbed visit'. When retreating from the feeder within five seconds after being butted, the visit was also considered 'interrupted'. Half of the visits were disturbed, and 42% of visits were also inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Competition for feed has previously been reported to increase aggressive interactions (DeVries et al, 2004), as well as to reduce feeding time and feed intake (DeVries and von Collings et al, 2011). It has also been reported to have disadvantageous effects on younger, smaller, newly calved, and high-yielding cows (Katainen et al, 2005;Val-Laillet et al, 2008;Huzzey et al, 2012). Feeding rate can be interpreted as an indicator of social pressure among group members (Nielsen, 1999;Collings et al, 2011), which suggests that competition had an adverse effect on lame primiparous cows in the current study.…”
Section: Associations With Lameness Scoressupporting
confidence: 50%
“…Competition for feed has previously been reported to increase aggressive interactions (DeVries et al, 2004), as well as to reduce feeding time and feed intake (DeVries and von Collings et al, 2011). It has also been reported to have disadvantageous effects on younger, smaller, newly calved, and high-yielding cows (Katainen et al, 2005;Val-Laillet et al, 2008;Huzzey et al, 2012). Feeding rate can be interpreted as an indicator of social pressure among group members (Nielsen, 1999;Collings et al, 2011), which suggests that competition had an adverse effect on lame primiparous cows in the current study.…”
Section: Associations With Lameness Scoressupporting
confidence: 50%
“…Similarly, de Vries et al [ 12 ] found a positive relationship between the presence of cow brushes and an increasing number of displacements. Competitive behaviour of dairy cows at a concentrate self-feeder were examined by Katainen et al [ 84 ]. The authors reported that nearly half of the visits (42%) at the concentrate feeder were interrupted by butting of other cows.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, an entrance-exit gate that protects the ewes while consuming their ration seems to be a necessity. Entrance-exit gates are not regularly used in commercial dairy herds, but Katainen et al (2005) showed that displacements from the EFS were quite frequent. For dry sows, all commercial models of EFS now have entrance-exit gates and usually also rear entry-side exit design (Hunter & Smith, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…For dairy cows the feeding station is just an open stall with an open rear entrance/exit, but Katainen et al (2005) observed that 42% of the visits to the feeding station were interrupted. An entrance gate to prevent bullying and displacements is considered to be a prerequisite in feeding stations for pigs (Edwards et al, 1988).…”
Section: Introductionmentioning
confidence: 99%